Možnosti upnika za zavarovanje denarne terjatve, kadar ima dolžnik premoženje v tujini - Kupec, Urška (Podjetje in delo, 2020)
The article examines the position of a creditor who wants to secure their monetary claim against a debtor with property abroad, where the creditor does not yet have a court decision, court settlement or public document, which is the basis of the creditor-debtor relationship. The author presents the procedure according to the relevant legal regulations, on the basis of which the creditor can obtain a legal title, preventing the debtor from disposing of the property abroad.
Keywords: denarna terjatev; European Account Preservation Order; interim injunction; monetary claim; nalog za zamrznitev bančnih računov; priznanje in izvršitev sodne odločbe; recognition and enforcement; začasna odredba